Pembenahan Strategi Pendidikan Dan Pelatihan Aparatur Sebagai Upaya Mendongkrak Kinerja Birokrasi Pemerintahan - Haris Faozan (Centre for Public Policy and Management Studies, 2004)
There have been so many kinds of training and development designed to improve the professionalism of government apparatus on managing public organization and delivering public services. The results, however, still show ineffectiveness. Based on this fact, this article try to give some suggestions on designing competence-based training. This training should be designed appropriate with strategic planning of the organization that there is a guarantee for good performance of the organization could be achieved. Besides, the training should be arranged with quality control mechanism by evaluation model on reaction level, behavioral level and result level. T his mechanism will support good feedback for training quality improvement.Kata Kunci: diktat, kompetensi, rencana strategis, model evaluasi